New Approaches to Systematics of Trypanosomatidae: Criteria for Taxonomic (Re)description - Votýpka, Jan; d'Avila-Levy, Claudia M; Grellier, Philippe; Maslov, Dmitri A; Lukeš, Julius; Yurchenko, Vyacheslav (Trends in parasitology, 2015)
While dixenous trypanosomatids represent one of the most dangerous pathogens for humans and domestic animals, their monoxenous relatives have frequently become model organisms for studies of diversity of parasitic protists and host-parasite associations. Yet, the classification of the family Trypanosomatidae is not finalized and often confusing. Here we attempt to make a blueprint for future studies in this field. We would like to elicit a discussion about an updated procedure, as traditional taxonomy was not primarily designed to be used for protists, nor can molecular phylogenetics solve all the problems alone. The current status, specific cases, and examples of generalized solutions are presented under conditions where practicality is openly favored over rigid taxonomic codes or blind phylogenetic approach.
Keywords: Phylogeny; fylogeneze; klasifikace; Classification; Parasitology; Trypanosomatina; parazitologie